"I will shoot them from my loving heart" : memoir of a South Korean officer in the Korean War - Hurh, Won Moo. (Jefferson, N.C. : McFarland & Co., 2012)
"In this memoir, Hurh provides not only a descriptive chronicle of his wartime exploits, but also a social psychological exploration on the absurdity of war in general. Hurh's vivid remembrances bring to life the "forgotten" Korean War from the viewpoint of a Korean soldier, a perspective rarely available in English until now"--Provided by publisher.
Chances of life -- My first life-chance -- Memories from the early years -- The war and my shattered life course -- Officer candidate school -- The frontline and Fort Sill -- Teaching at the ROK artillery school -- Back to the front -- Antiaircraft artillery and Fort Bliss -- Serving the top brass -- Epilogue -- Appendix: ROK infantry and artillery (1950-53).
Includes bibliographical references (p. 181-182) and index.
Keywords: Korean War, 1950-1953 -- Personal narratives, Korean; Korean War, 1950-1953 -- Artillery operations; Soldiers -- Korea -- Biography